Stay Mindful and Carry on: Mindfulness Neutralizes COVID-19 Stressors on Work Engagement via Sleep Duration - Zheng, Michelle Xue; Masters-Waage, Theodore Charles; Yao, Jingxian; Lu, Yizhen; Tan, Noriko; Narayanan, Jayanth (Frontiers in Psychology, 2020)
We examine whether mindfulness can neutralize the negative impact of COVID-19 stressors on employees’ sleep duration and work engagement. In Study 1, we conducted a field experiment in Wuhan, China during the lockdown between February 20 and March 2 2020 in which we induced state mindfulness by randomly assigning participants to either a daily mindfulness practice or a daily mind-wandering practice. Results showed that the sleep duration of participants in the mindfulness condition, compared with the control condition, was less impacted by COVID-19 stressors (i.e. the increase of infections in the community). In Study 2, in a 10-day daily diary study in the United Kingdom between June 8 and June 19 2020, we replicate our results from Study 1 using a subjective measure of COVID-19 stressors and a daily measure of state mindfulness. In addition, we find that mindfulness buffers the negative effect of COVID-19 stressors on work engagement mediated by sleep duration. As the COVID-19 pandemic is ongoing and the number of reported cases continues to rise globally, our findings suggest that mindfulness is an evidence-based practice that can effectively neutralize the negative effect of COVID-19 stressors on sleep and work outcomes. Findings of the present study contribute to the employee stress and well-being literature as well as the emerging organizational research on mindfulness.